Influence of heating on stability of γ-oryzanol in gluten-free ready meals - Kalmazan, Viktoria; Yanenko, Larisa (My University, 2016)
Rice is a rich source of γ-oryzanol, which is a mixture of lipophilic phytosterols composed of triterpene alcohols or sterols with ferulic acid ester. In recent years the usefulness of γ-oryzanol has been especially studied and highlighted for the treatment of diseases.
Keywords: thermal oxidation; treatment of diseases; rice; γ-oryzanol; термічне окислення; лікування захворювань; рис; γ-оризанол; термическое окисление; лечение заболеваний; кафедра іноземних мов професійного спрямування